Speech of Patients With Unilateral Complete Cleft Lip and Palate: Comparison of Three Different Surgical Protocols for Primary Repair. Issue 3 (May 2020) - Ahti, Veera; Alaluusua, Suvi; Rautio, Jorma; Leikola, Junnu; Hukki, Jyri; Saarikko, Anne
Abstract : Background and Aims: Between 1997 and 2014, 3 protocols have been used in out cleft unit for primary repair of unilateral cleft lip and palate. During the Scandcleft randomized controlled trial closing the soft palate and lip at 4 months and the hard palate at 12 months (Protocol 1) was compared with closing the entire palate at 12 months (Protocol 2). Protocol 3 comprises closure of the lip and hard palate with a vomer flap at 4 months and the soft palate at 10 months. The purpose of this study was to compare subsequent velopharyngeal competence at age of 3 and 5 years. Patients and Methods: The study consisted of 160 non-syndromatic patients with a unilateral cleft lip and palate. Protocol 3 was retrospectively compared with Protocols 1 and 2 within the previously published Scandcleft study. Results: At 3 years of age, normal or borderline competent velopharyngeal function was found in 68% of patients in Protocol 1, 74% of patients in Protocol 2, and 72% of patients in Protocol 3. At 5 years of age, the corresponding figures were 84%, 82%, and 92%. 21% of patients in Protocol 1, 4% in Protocol 2, and 23% in Protocol 3 had palatal reoperations before the age of 5 years. Conclusion: No significant differences emerged in velopharyngeal competence at age 3 years between the 3 protocols. Palatal reoperations were performed earlier in patient groups 1 and 3, explaining the difference in the velopharyngeal competence rate at the 5-year time-point. Abstract : Supplemental Digital Content is available in the text